Geographic and racial variation in asthma prevalence and emergency department use among Medicaid-enrolled children in 14 southern states. (November 2014) - Malhotra, Khusdeep; Baltrus, Peter; Zhang, Shun; McRoy, Luceta; Immergluck, Lilly Cheng; Rust, George
Abstract Background: Despite evidence-based prevention and practice guidelines, asthma prevalence, treatment, and outcomes vary widely at individual and community levels. Asthma disproportionate/ly affects low-income and minority children, who comprise a large segment of the Medicaid population. Methods: 2007 Medicaid claims data from 14 southern states was mapped for 556 counties to describe the local area variation in 1-year asthma prevalence rates, emergency department (ED) visit rates, and racial disparity rate ratios. Results: One-year period prevalence of asthma ranged from 2.8% in Florida to 6.4% in Alabama, with a median prevalence rate of 4.1%. At the county level, the prevalence was higher for Black children and ranged from 1.03% in Manatee County, FL, to 21.0% in Hockley County, TX. Black–White rate ratios of prevalence ranged from 0.49 in LeFlore County, MS, to 3.87 in Flagler County, FL. Adjusted asthma ED visit rates ranged from 2.2 per 1000 children in Maryland to 16.5 in Alabama, with a median Black–White ED-visit rate ratio of 2.4. Rates were higher for Black children, ranging from 0.80 per 1000 in Wicomico County, MD, to 70 per 1000 in DeSoto County, FL. Rate ratios of ED visits ranged from 0.25 in Vernon Parish, LA, to 25.28 in Nelson County, KY. Conclusions and relevance: Low-income children with Medicaid coverage still experience substantial variation in asthma prevalence and outcomes from one community to another. The pattern of worse outcomes for Black children also varies widely across counties. Eliminating this variation could substantially improve overall outcomes and eliminate asthma disparities.